Exploring drought risk scenarios for bioenergy systems for adaptation to climate change in the Upper Tocantins basin, Brazil - Jazmin Campos Zeballos; Vinicius Bof Bufon; Zita Sebesvari; Jakob Rhyner (Environmental Advances)
The generation of electricity from sugarcane bagasse plays an important role in Brazil's energy mix, particularly in complementing hydropower during the dry season and in mitigating the impacts of climate change. However, sugarcane is facing increasing challenges due to the occurrence of droughts. This study assesses drought risk of sugarcane, with a particular focus on its role in bagasse-based electricity generation. The IPCC AR5 Risk Assessment Framework was employed to evaluate two global climate change models, two representative concentration pathways (RCPs), and three land use scenarios. The present study employs a dynamic approach to analyse the interconnectivity of risk components, thereby contributing to the development of a methodology to compare risk scenarios considering changes in the system. Spatial analyses of hazard, exposure, and vulnerability were conducted, revealing dynamic risk across nine scenarios. This highlights the necessity of understanding the interconnectivity for a comprehensive risk analysis and the implementation of effective measures to mitigate risk. The findings emphasise the necessity of tailored risk management strategies to effectively address drought risks, focusing on the planning of sugarcane expansion and, more specifically, on the reduction of vulnerability. The results indicate that the reduction of vulnerability is dependent on the implementation of early warning systems, which serve as a crucial mechanism for the timely dissemination of drought information. Furthermore, access to water reservoirs (e.g. dams) and the implementation of efficient irrigation systems play a pivotal role in enhancing resilience and reduce further vulnerability within the sector. The analysis facilitates the identification of the strengths and the weaknesses of the systems for the implementation of targeted mitigation measures. These measures are intended to strengthen the sector's resilience and sustainability, aligning with national objectives.